Formulation and evaluation of novel collagen/ carboxymethylcellulose blend film wound dressing - Tenorová, Kateřina; Kurfürstová, Jana; Masteiková, Ruta; Pavloková, Sylvie; Bernatonien, Jurga (Ceska a Slovenska farmacie, 2022)
Films are thin, flexible, and transparent wound dressings. They can be prepared from both synthetic and natural materials. In practice, synthetic polyurethane dominates, but research is mainly focused on substances of natural origin. An endogenous substance with excellent filmforming properties, which is involved in the wound healing process, is collagen. However, collagen films themselves have weak mechanical properties, which can be improved by, among other things, combining collagen with other materials. Such material could be carboxymethylcellulose, which has been shown to affect wound healing positively. Films consisting only of CMC also have weak mechanical properties, so combining both materials seems to be a suitable solution to the given problems, and a wound dressing with many beneficial properties for wound healing could be created. Therefore, our experiment aimed to prepare composite films for wound therapy consisting of a combination of collagen and CMC. The films were prepared by the solvent evaporation method, and their properties were compared with those formed only by CMC. In both cases, films with suitable organoleptic, physicochemical, and application properties for wound therapy were produced. The composite films showed lower absorption capacity and better mechanical resistance compared to those formed only by CMC. The combination of collagen and CMC in composite films intended for wound therapy has thus resulted in improved properties of the resulting dressing and holds potential for further research.
Keywords: kolagen; Carboxymethylcellulose Sodium; sodná sůl karboxymethylcelulosy; Wound Healing; polyurethany; carboxymethylcellulose; evaluation; collagen; film wound dressing; Bandages; obvazy; blend films; hojení ran; Collagen; Polyurethanes